Applying Recurrent Neural Networks with Long Short-Term Memory in Clustered Stocks - Affonso, Felipe; Dias, Thiago Magela Rodrigues (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e Computacional, 2018)
Predicting the stock market is a widely studied field, either due to the curiosity in finding an explanation for the behavior of financial assets or for financial purposes. Among these studies the best techniques use neural networks as a prediction tool. More specifically, the best networks for this purpose are called recurrent neural networks (RNN), and provide an extra option when dealing with a sequence of values. However, a great part of the studies is intended to predict the result of few stocks, therefore, this work aims to predict the behavior of a large number of stocks. For this, similar stocks were grouped based on their correlation and later the algorithm K-means was applied so that similar groups were clustered. After this process, the Long Short-Term Memory (LSTM) - a type of RNN - was used in order to predict the price of a certain group of assets. Results showed that clustering stocks did not influence the effectiveness of the network and that investors and portfolio managers can use it to simply their daily tasks.